Comunidades de prática online para as bibliotecas dos colégios de aplicação das IFES: um espaço de discussão sobre a mediação da leitura e da informação - Valdez, Tatyanne (2015)
Discusses the mediation of reading and mediation of information in the context of school libraries. It presents a proposal for the creation of a community of online practice so the professionals who act in the application school's libraries of the Federal Institutions of Higher Education (FIHE) can exchange information and experience about the mediation of reading and of information. Thus, verifies wich are the mediation actions developed on the application school's libraries of the Federal Institutions of Higher Education (FIHE). Also, pretends to identify the understanding of the librarians on the application schools regards the mediation of reading and the mediation of information as actions who contribute to the students learning process. Besides, try to discover what is the best internet platform to configure a online practice comunity. To do so, adopts a qualitative methodology, with exploratory character, to reach the purposes of this work. The universe of the field research were the seventeen libraries of the FIHEs' application schools and the instruments used to collect data were questionnaires and interviews with five librarians. In this matter, the content analysis was used as the technique to process the data collected. The research result shows the important informations about the activities of mediation of reading and mediation of information who are realized by the application schools' libraries. It confirms that Facebook is the ideal social media to the implementation of an online practice community to these professionals and also provides the the tools for debates about their practice.